2009
DOI: 10.1111/j.1463-1318.2008.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative course and long term follow up after colectomy for slow transit constipation – is surgery an appropriate approach?

Abstract: Morbidity and mortality rate after colectomy were inadmissibly high. Taking into account the poor functional results, we cannot recommend colectomy for slow transit constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…Describing their experience with subtotal colectomy and ileo-rectal anastomosis for idiopathic constipation in adult patients, Austrian surgeons reported 15% mortality and a 50% reoperation rate 16. Clearly, these results are unacceptable, and although it might be expected that adult patients would bring more comorbidities to surgery than children, why their results should be so much worse when utilising a lesser procedure than the current series is highly surprising.…”
Section: Discussionmentioning
confidence: 62%
“…Describing their experience with subtotal colectomy and ileo-rectal anastomosis for idiopathic constipation in adult patients, Austrian surgeons reported 15% mortality and a 50% reoperation rate 16. Clearly, these results are unacceptable, and although it might be expected that adult patients would bring more comorbidities to surgery than children, why their results should be so much worse when utilising a lesser procedure than the current series is highly surprising.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, some studies reported a high postoperative complication rate [24, 25]. Knowles et al [26] analyzed 31 research papers published from 1981 to 1998 and found that the rates of small bowel obstruction and reoperation were 18% and 14%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mean success rate for these interventions is reported to be high, around 89% . However, postsurgical adverse events are described in up to 45% of patients . In addition, mortality is considerable when an anastomosis is made .…”
Section: Discussionmentioning
confidence: 99%
“…When all conservative measures fail, surgical treatments such as appendicostomy, ileostomy with colonic exclusion, or segmental or total colectomy are considered . Previous reports demonstrate variable efficacy of these surgical treatment entities, and morbidity of these procedures is high . Less invasive and potentially reversible procedures such as sacral neuromodulation and tibial nerve stimulation have been disappointing with respect to efficacy .…”
Section: Introductionmentioning
confidence: 99%